INFLUENCE OF METEOROLOGICAL PARAMETERS ON AIR QUALITY AND OTHER POLLUTANTS IN DUHOK CITY, IRAQ - & et al., Mahdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigated the relationship between the daily average of meteorological parameters (MP), and the daily average (DA) of air pollutant concentrations (PC) (including particulate matter (PM)). In this study, the DA of air PC, such as carbon monoxide (CO) and sulphur dioxide (SO2), was measured during heavy traffic in the summer season for five different locations throughout 2017, and comparison made with results similarly obtained in 2012. The particulate matter sample has been collected for the same period. The daily average meteorological parameters (MP) such as temperature (T), atmospheric pressure (AP), wind direction (WD), wind speed (WS) and relative humidity (RH) were measured and collected from the Directorate of Meteorology and Seismology Instrument at DC during the same period. The microstructure and morphology of the particles have been investigated using scanning electron microscopy (SEM), and reflected light microscopy (RLM). The chemical composition of the particles has been studied using energy-dispersive X-ray (EDX) and atomic absorption spectrometry (AAS). The EDX analysis shows that silicon and calcium were found to be the most abundant elements in the dust particles. Mineralogical characterization was carried out using X-ray diffraction (XRD), and results of which indicate the presence of calcium carbonate (CaCO3).